THUR 179 Ocrelizumab effect on neda in patient subgroups of opera I and opera II. Issue 10 (13th September 2018) - Ben, Turner; Caroline, Papeix; Bruce, Cree; Ludwig, Kappos; Xavier, Montalban; Jerry, Wolinsky; Regine, Buffels; Jian, Han; Stephen, Hauser
Abstract : Background: In a pooled analysis of patients with relapsing multiple sclerosis in the Phase III OPERA I and OPERA II (NCT01247324 /NCT014112333) studies, ocrelizumab increased the proportion of patients with no evidence of disease activity (NEDA) vs interferon β−1a (IFNβ1a); post hoc subgroup analyses are reported here. Methods: NEDA (no 12 week confirmed disability progression, relapse, new/enlarging T2 lesions or T1 gadolinium enhancing lesions) rates were compared by Cochran–Mantel–Haenszel test on the pooled modified intent-to-treat (mITT) population (ocrelizumab, n=761 [600 mg intravenously every 24 weeks]; IFNβ1a, n=759 [44 μg subcutaneously three times weekly]; excludes patients with NEDA discontinuing for reasons unrelated to efficacy). Results: Treatment benefit for NEDA in the mITT population with ocrelizumab vs IFNβ1a (47.7% vs 27.1%; p<0.001) was maintained across subgroups (ocrelizumab/IFNβ1a; p<0.001 unless stated): age (<40 years: 44.3%/22.6%; ≥40 years: 52.8%/33.7%), gender (male: 44.0%/22.2%; female: 49.7%/29.6%), prior [last 2 years] disease-modifying therapy (yes: 42.8%/23.9%; no: 49.5%/28.3%), prior relapses [last 12 months] (≤1: 49.2%/29.2%; ≥2: 44.2%/22.6%), baseline T1 Gd-enhancing lesions (none: 59.6%/38.8%; ≥1: 30.1%/10.2%) and baseline EDSS score (EDSS <2.5/<4.0: ocrelizumab 50.5%/50.3%, IFNβ1a 27.5%/26.4%; EDSS ≥2.5/≥4.0: ocrelizumab 46.0%/39.6%, IFNβ1a 26.9%/29.4% [NB: EDSS score ≥4: ocrelizumab/IFNβ1a p=0.043]). Conclusions: Subgroup analyses were consistent with those of the overall pooled population on maintaining NEDA status.